ALEX2014: The Alqueva Hydro-Meteorological Experiment - Salgado, Rui (2015)
During the four months of the ALEX 2014, the over water fluxes of momentum, heat and mass (H2O and CO2) were obtained with an integrated Open-Path CO2 /H2O Gas Analyser and 3D Sonic Anemometer, mounted on a floating platform (Fig.1) belonging to the Portuguese Environment Agency. The short and long wave, up and down, radiative fluxes were measured at the same place, as well as the water temperature profile. Eight near surface weather stations were operating during the field campaign, two in floating platforms and one in a little island. The air quality, the atmospheric electrical field (Potential Gradient) and the radon (222Rn) concentration were continuous monitored. The solar direct normal irradiation (DNI) as well as other solar radiation components were also measured. Along this period, in situ measurements, water sam-ples and biological elements were monthly collected from three fixed platforms placed in the lacustrine zone and from selected sites in the margins. In each campaign, the vertical profiles of temperature, dis-solved oxygen (mg DO L-1 and %), pH, oxidation-reduction potential, turbidity and solar inwater irra-diation were taken. Simultaneously, water samples were collected at three depths for nutrient determina-tion and microscopic and molecular characterization of cyanobacteria. Diatoms were collected from artificial substrates placed in the platforms and Chironomid pupal exuviae were sampled from two selected sites on the reservoir margins During the IOP, 18 balloons with meteorological radiosondes were launched. In 10 occasions Geigersondes were coupled to the radiosondes in order to obtain the atmospheric ionization profile. The boundary layer was characterized with a Ceilometer and the vertical distribution of O3 and NO2 were obtained from a Spectrometer. A GPS network of 15 GNSS stations was installed in order to map the water vapour. The sky brightness on the nights of July 24 and 25, was measured using a Sky Quality Meter.